1998
DOI: 10.1093/ps/77.6.820
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional aspects of hydrogenated and regular soybean oil added to diets of broiler chickens

Abstract: The objective of the present study was to evaluate the effect of degree of saturation of fat incorporated into broiler diets on performance and body fatty acid (FA) profile. The various degrees of saturation were achieved by using regular soybean oil (SO) and hydrogenated soybean oil (HSO), mixed at different proportions. The work was carried out on commercial broilers (Experiment 1) and on lines of chickens divergently selected for high (HF) or low (LF) abdominal fat (Experiment 2). Daily BW gain and gain:fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 20 publications
1
18
1
3
Order By: Relevance
“…Some papers report that the profile of fatty acids, such as the length of the carbon chain, the number of double bonds and the fatty acid position in the glycerol molecule strongly influence digestibility (Renner and Hill, 1961;Dvorin et al, 1998;Crespo and EsteveGarcia, 2001). Lara et al (2005) added to these factors the amount of triglycerides or free fatty acids that are present in the lipid composition.…”
Section: Introductionmentioning
confidence: 99%
“…Some papers report that the profile of fatty acids, such as the length of the carbon chain, the number of double bonds and the fatty acid position in the glycerol molecule strongly influence digestibility (Renner and Hill, 1961;Dvorin et al, 1998;Crespo and EsteveGarcia, 2001). Lara et al (2005) added to these factors the amount of triglycerides or free fatty acids that are present in the lipid composition.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that birds have the ability to utilize significant amounts of dietary fat as a source of energy; however, the efficiency of its utilization largely depends on the composition of fatty acids (Latour et al, 1994;Scaife et al,1994;Peebles et al,1997a,b,c;Dvorin et al, 1998;Zdunczyk et al, 2001;Ozdogan and Ak §it, 2003;Shahriar et al, 2007). It was shown that animal fats rich in saturated fatty acids are more difficult to digest in the digestive system of poultry as compared to unsaturated vegetable oils (Dvorin et al, 1998;Zdunczyk et al, 2001). The importance of fat from different sources in the feeding of broilers is analysed not only from the aspect of production effects, but also in the context of human health.…”
Section: Introductionmentioning
confidence: 99%
“…Oils with PUFA produce higher energy and upgrade the performance, because compared to oils that contain saturated fatty acids they are absorbed easier consequently, as explained by Dvorin et al (1998), birds fed on diet containing high levels of PUFA have better BWG. Moreover, digestion and absorption of dietary fat depend also on the age of the birds (Burlikowska et al, 2010).…”
Section: Effects Of Dietary Inclusion Of Oil Sources With or Without mentioning
confidence: 99%